Investigation of Host Factors Required for Lymphocytic Choriomeningitis Virus Entry - Gould Maule, Graham (Université d'Ottawa / University of Ottawa, 2019)
Lymphocytic choriomeningitis virus (LCMV) is an old-world arenavirus capable of causing severe diseases in humans. Despite the extensive use of LCMV in studying immune responses to viral infection, very little is known about its entry pathway. As an enveloped virus, the main determinant of LCMV entry is the viral glycoprotein, which allows for the fusion of the viral membrane with that of the target cell, upon specific triggers. While the exact triggers for LCMV GP are currently unknown, low pH and interaction with a yet to be identified host-encoded receptor are likely involved in the activation of the GP fusion activity. This thesis finds that a triad of histidine residues on LCMV’s GP is absolutely critical for infection. Since mutation of the histidine triad had no effect on GP synthesis and did not completely abrogate its ability to bind to cells, our data suggest that the histidine triad are important for a step after virus internalization, potentially allowing low pH sensing. In addition, through the use of engineered soluble GPs, pulldown experiments, and mass spectrometry, various LCMV receptor candidates were identified. These candidates were further validated in order to identify crucial host proteins involved in LCMV entry. This study finds that LCMV GP interacts strongly with the Neuropilin proteins NRP1 and NRP2, and these cellular proteins may play a role in LCMV’s entry pathway during infection.
Keywords: LCMV; Entry